2010
DOI: 10.1111/j.1834-7819.2010.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucosal malignancy and potentially malignant lesions: an update on the epidemiology, risk factors, diagnosis and management

Abstract: An oral examination for the assessment for malignant and potentially malignant oral mucosal lesions is routine in general dental practice. It may be uncommon for general dental practitioners to encounter oral cancer, with anecdotal reports suggesting that this occurs about once every 10 years in a busy general dental practice. However, potentially malignant oral mucosal lesions are relatively common, occurring in about 2.5% of the population. This update highlights the epidemiology, risk factors, diagnosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
136
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(149 citation statements)
references
References 33 publications
(43 reference statements)
0
136
0
2
Order By: Relevance
“…1 Potentially malignant lesions of oral cavity are relatively common occurring in about 2.5% of the population with a malignant transformation rate of 0.6 to 20% as reported in various studies and locations. 3 Identification of molecular markers in blood would predict the development of cancer in its earliest stage or in precancerous stage. Literature scan reveals very few studies on RBC indices and role of WBC count in the diagnosis of malignancies of the head and neck.…”
Section: Blood Urea and Creatininementioning
confidence: 99%
“…1 Potentially malignant lesions of oral cavity are relatively common occurring in about 2.5% of the population with a malignant transformation rate of 0.6 to 20% as reported in various studies and locations. 3 Identification of molecular markers in blood would predict the development of cancer in its earliest stage or in precancerous stage. Literature scan reveals very few studies on RBC indices and role of WBC count in the diagnosis of malignancies of the head and neck.…”
Section: Blood Urea and Creatininementioning
confidence: 99%
“…13,14 The reported five-year survival rate of stage III or IV oral cancer ranges between 15% and 55%. [15][16][17][18] In contrast, oral cancers diagnosed at a smaller size and without lymph node involvement in stage I or II report a five-year survival rate ranging between 66% and 85%. 11,15,19 A recent analysis of 22,204 pathologically verified oral cancers followed up over ten years concluded that early diagnosis and intervention before stage II can significantly improve life expectancy and decrease expected years of life lost to oral cancer.…”
Section: Chapter One: Introductionmentioning
confidence: 99%
“…[15][16][17][18] In contrast, oral cancers diagnosed at a smaller size and without lymph node involvement in stage I or II report a five-year survival rate ranging between 66% and 85%. 11,15,19 A recent analysis of 22,204 pathologically verified oral cancers followed up over ten years concluded that early diagnosis and intervention before stage II can significantly improve life expectancy and decrease expected years of life lost to oral cancer. 18 This is ideally when the patient is likely asymptomatic with a tumour less than 2cm in diameter and with less than 4mm of invasion.…”
Section: Chapter One: Introductionmentioning
confidence: 99%
See 2 more Smart Citations